Myopericarditis in tuberculous pericardial effusion: prevalence, predictors and outcome. Issue 2 (19th November 2013) - Syed, Faisal F; Ntsekhe, Mpiko; Gumedze, Freedom; Badri, Motasim; Mayosi, Bongani M
Abstract : Objective: The prevalence, predictors and outcome of myopericarditis in patients with tuberculous (TB) pericarditis are unknown. Methods: Eighty-one patients (mean age±SD, 36.1±13.3 years; 54 (66.7%) men; 58 (71.6%) HIV seropositive) with TB pericarditis were recruited between January 2006 and September 2008. Myopericarditis was defined as echocardiographic LV systolic dysfunction (immediately after pericardiocentesis), elevated peripheral blood troponin T (>0.03 ng/mL), or elevated peripheral blood creatine kinase (CK >174 IU/L) with a CK:CK-myocardial band (MB) mass ratio of >6%. The outcome measure was case fatality rate at 6 months of follow-up. Results: Myopericarditis was present in 43 (53.1%) patients. Patients with myopericarditis, as compared with those without, were more likely to be HIV seropositive (35 (81.4%) vs 23 (60.5%) respectively, p=0.038) and have lower peripheral CD4 count (median (IQR) 98 (54–290) vs 177 (104–429), p=0.026). Electrocardiographic ST segment elevation was more common in myopericarditis (15 (36.6%) vs 4 (10.8%), p=0.008) and predicted myopericarditis independently of CD4 count on multiple logistic regression analysis (OR 4.36, 95% CI 1.34 to 17.34, p=0.0132). At 6 months, 14 (18%) patients had died with no significant difference between those with or without myopericarditis (6/42 (14%) vs 8/36 (22%), respectively (p=0.363)). Conclusions: Myopericarditis is common in TB pericardial effusion and associated with HIV-related immunosuppression. It can be identified by electrocardiographic ST-elevation, particularly when peripheral CD4 count is low. There was no significant difference in case fatality rate in those with or without myopericarditis.